Therapeutic approach: prophetic etiquette - Md Rosli, Ahmad Nabil (2019)
Islam emphasizes the importance of good manner or etiquette as a part of one's personal psycho-spiritual development. While the values inherited in these etiquette are spiritual-religious in nature and are believed to benefit the practitioner, they serve certain therapeutic values to other people. This article will discuss some of the therapeutic approach which are derived from both; Islamic and modern empirical sources e.g. positive regards, empathy, compassion, emotional expression, and sincerity, which can be integrated and emulated in psychotherapy. The challenges and limitations will be highlighted.